1992
DOI: 10.2224/sbp.1992.20.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Videogames, Aggression, and Self-Esteem: A Survey

Abstract: A survey was administered to 153 sixth through twelfth graders. It included items on videogame play plus self-esteem and aggression scales. Teachers also rated the children on self-esteem and aggression. Amount of videogame play correlated with aggression and not with self-esteem. About 4796 of the sample said some videogames might foster anger or aggression. Among other results was evidence that boys play videogames more than girls and are more aggressive than girls. Self-esteem and aggression were positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 11 publications
1
30
0
4
Order By: Relevance
“…Consistently, correlational and experimental research has linked exposure to media violence with increases in aggressive behavior, thoughts, and feelings in children, adolescents, and young adults [Anderson and Bushman, 2001;Anderson and Dill, 2000;Ballard and Lineberger, 1999;Fling et al, 1992;Griffiths and Hunt, 1995]. Moreover, the effect sizes for media violence and aggression tend to be stronger than the effect sizes for condom use and sexually transmitted HIV, passive smoking and lung cancer at work, exposure to lead and IQ scores in children, nicotine patch and smoking cessation, and calcium intake and bone mass [Anderson and Bushman, 2001].…”
Section: Introductionmentioning
confidence: 93%
“…Consistently, correlational and experimental research has linked exposure to media violence with increases in aggressive behavior, thoughts, and feelings in children, adolescents, and young adults [Anderson and Bushman, 2001;Anderson and Dill, 2000;Ballard and Lineberger, 1999;Fling et al, 1992;Griffiths and Hunt, 1995]. Moreover, the effect sizes for media violence and aggression tend to be stronger than the effect sizes for condom use and sexually transmitted HIV, passive smoking and lung cancer at work, exposure to lead and IQ scores in children, nicotine patch and smoking cessation, and calcium intake and bone mass [Anderson and Bushman, 2001].…”
Section: Introductionmentioning
confidence: 93%
“…In a more recent survey of 153 typical adolescents and adolescents with diagnosed emotional disturbance (sixth through twelfth graders, 49 girls), Fling et al [1992] demonstrated a positive correlation between self-reported frequency of playing any kind of video games and self-reports of aggressive behavior. This finding was not replicated in a similar survey of 346 typical seventh and eighth graders by Van Schie and Wiegman [1997].…”
Section: Time Spent Playing Electronic Gamesmentioning
confidence: 97%
“…Veliki broj korelacionih studija ukazuje na to da postoji značajna pozitivna korelacija između izloženosti nasilju u video-igricama i agresivnog ponašanja (Anderson i Dill, 2000;Anderson et al, 2007;Dominic, 1984;Fling et al, 1992;Lin i Lepper, 1987). Efekat izloženosti nasilju u igricama na agresivno ponašanje ostaje i kada se uzmu u obzir značajne moderatorske varijable.…”
Section: Povezanost Igranja Nasilnih Video-igrica I Agresivnog Ponašanjaunclassified
“…Iz toga zaključujemo da bi bilo pogrešno svesti početnu povezanost između nasilnosti video-igrica i vršnjačkog nasilja na uticaj pola, uzrasta i gledanja nasilnih TV sadržaja. Naši nalazi su u saglasnosti sa rezultatima autora koji su se bavili povezanošću igranja nasilnih igrica i agresivnog ponašanja uopšte, pri čemu su dobijani mali, ali značajni efekti (Anderson i Dill, 2000;Anderson et al, 2007,;Dominic, 1984;Fling et al, 1992;Griffiths, 1999;Lin i Lepper, 1987). Rezultati su saglasni i sa nalazima Bilićeve o povezanosti igranja nasilnih igrica i gledanja nasilnih TV sadržaja i vršnjačkog nasilja (Bilić, 2010).…”
Section: Diskusijaunclassified